(3JGQjN GdMceGAs - (3LeGd GdOjf Ydj Hf jhSas; (3GdbaWj , LeGd GdOjf CHh GdMSf,J (B646 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdbOje GdGRd hHYO aEf JhGQjN GdMceGA GdCbOejf hGdadGSaI GdeJGdgjf ef GdjhfGfjf hGdeUQjjf jLH Ydi GdeSJHUQ JMUjdg hYdi GdMcje JYdeg hJYdjeg s
(3BNQgG (B:s
(3hdh cGfJ GdOfjG efGSHI dgG deG GSJMVQJ fbUGfgG hceGdgG JaSjQ ShQI GdHbQYg GdhLg GdYbd dG Gdfbd s
(3fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B33 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B263s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQVhjI (B- (3eTgO (B(4086) s
Keywords: (3GdJGQjNs